Diagnostic features of SARS‐COVID‐2‐positive patients: A rapid review and meta‐analysis. Issue 13 (17th February 2021) - Anderson, Gloria; Casasanta, Daniela; Cocchieri, Antonello; D'Agostino, Fabio; Zega, Maurizio; Damiani, Gianfranco; Rega, Maria Luisa
Abstract: Aims: To identify the main diagnostic features of SARS‐CoV‐2‐positive patients at the time of hospitalisation and their prevalence. Background: Since the COVID‐19 outbreak in China in December of 2019, several studies attempted to identify the epidemiological, viral and clinical characteristics of SARS‐CoV‐2. Given the rapid widespread transmission of the COVID‐19 disease worldwide, a more comprehensive and up‐to‐date understanding of its features is needed to better inform nurses, clinicians and public health policy makers. Methods: A rapid review and meta‐analysis were carried out to identify the main diagnostic features of SARS‐CoV‐2‐positive patients at the time of hospitalisation. All case series, cross‐sectional, case–control and cohort studies published from 01/01/2020 till 30/06/2020 in English and Chinese that stated all or at least two of the outcomes of interest (clinical features, laboratory and radiological findings) were included. We performed a random‐effects model meta‐analysis to calculate pooled prevalence and 95% confidence intervals. Conduction of the review adheres to the PRISMA checklist. Results: 21 studies involving 8837 patients were included in the quantitative synthesis. Fever, cough and fatigue were the most common clinical features, while the most relevant laboratory abnormalities at the time of hospitalisation were lymphopenia, elevated C‐reactive protein and lactate dehydrogenase. CT images showed a bilateral lung involvement, with ground glass infiltrates and patchy shadows on most patients. Conclusion: This review provides an up‐to‐date synthesis of main diagnostic features of SARS‐CoV‐2‐positive patients at the time of hospitalisation. Relevance to Clinical Practice: Our findings could provide guidance for nurses and clinicians to early identification of positive patients at the time of the hospitalisation through a complete definition of main clinical features, laboratory and CT findings.